Contextualization of Grade 7 Reading Instruction Through React Strategy - Loverita, Claudette (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of contextualized Grade 7 reading instruction through the REACT Strategy in improving students' reading comprehension and determining their learning gains as inputs for the development of a reading training matrix. The study was anchored on Contextual Learning Theory (CTL), the REACT Strategy (Relating, Experiencing, Applying, Cooperating, and Transferring), and Coombs' System Approach. A quantitative quasi-experimental research design was employed involving 422 Grade 7 students from 13 sections of Pitogo High School during the School Year 2025–2026. A validated researcher-made 25-item pretest and posttest, supported by a Table of Specifications and implemented through contextualized Daily Lesson Logs, served as the primary research instruments. Data were analyzed using mean, standard deviation, and paired t-test. The findings revealed that students achieved a satisfactory level of learning before the intervention (M = 18.30, SD = 3.451) and a very satisfactory level after the implementation of contextualized reading instruction through the REACT Strategy (M = 21.983, SD = 1.994). The paired t-test confirmed a significant difference between the pretest and posttest scores, indicating that the intervention effectively improved students' reading comprehension. Students demonstrated enhanced ability to understand texts, identify key ideas and supporting details, infer meanings, and relate textual information to real-life experiences. These learning gains served as the basis for developing a teacher training matrix to strengthen contextualized reading instruction and improve instructional practices. The study concludes that contextualized reading instruction through the REACT Strategy is an effective approach for enhancing students' reading comprehension and recommends its continued implementation, supported by teacher training and regular monitoring. This study supports Sustainable Development Goal 4 (Quality Education) by promoting learner-centered, contextualized reading instruction that improves literacy and learning outcomes. Its sustainability impact lies in strengthening instructional practices and supporting the long-term development of effective, evidence-based reading programs in schools.
Keywords: Contextual Learning Theory; Grade 7 Reading Instruction; Learning Gains; Reading Comprehension; REACT Strategy; Reading Training Matrix